Le recensement des outils de travail disponibles en français pour les professionnels oeuvrant dans le domaine de la santé : un rapport de la méthodologie utilisée par les physiothérapeutes - Casimiro, Lynn; Fortin, Murielle; Moisan, France; Tremblay, Louis E. (Reflets, 2002)

Santé des organismes communautaires inc. - Nolet, Lise (Reflets, 1999)
Cet article décrit la création et le mandat de Santé des organismes communautaires inc. (SOCI), un nouvel organisme à but non-lucratif qui a été créé pour administrer le programme de révisions et d’accréditation des Centres de santé communautaires (CSC) en Ontario. Il existait, au moment de sa création, 54 CSC en Ontario, dont cinq qui offraient uniquement des services en français.

Problèmes d’accès aux services en français ? Contactez-nous. Nous pouvons vous aider [infographie] - Ombudsman de l'Ontario (2022)

Problems accessing services in French? Contact us. We can help [infographie] - Ontario Ombudsman (2022)

An evaluation of FrancoForme: A case-managed home-based primary and secondary cardiovascular disease prevention program for French-speaking Canadians - Prince, Stephanie. A.; Laflamme, Marc; Harris, Jennifer; Tulloch, Heather E.; de Margerie, Michele (Journal of cardiopulmonary rehabilitation and prevention, 2017)
Purpose: Cardiovascular disease (CVD) is the leading cause of mortality globally. Telephone-delivered interventions targeting cardiovascular risk factors are gaining popularity. This study is an evaluation of FrancoForme, a cardiovascular risk factor reduction program for the primary and secondary prevention of CVD among French-speaking patients of Eastern Ontario. Methods: This study reports on changes in cardiovascular risk factors, weekly exercise levels, and psychosocial characteristics including anxiety, depression, and quality of life upon program completion (3 months) and at 1 year after the start of the program. Repeated-measures analysis of variance was used to compare changes in outcomes between primary prevention risk groups (low, moderate, and high risk for CVD) and the secondary prevention group (ie, cardiac rehabilitation) at baseline, 3 months and 12 months. Results: A total of 762 patients enrolled in FrancoForme between 2008 and 2015. At 3 months, all program completers (n = 507) experienced significant reductions for all cardiovascular risk factors except diastolic blood pressure. Minutes of self-reported exercise increased significantly by an average 90 minutes per week and all psychosocial variables improved. Significant group effects were observed across several risk factors. Among 12-month responders (n = 240), exercise, high-density lipoproteins, triglycerides, cholesterol, and all psychosocial variables were improved over baseline results. Conclusions: FrancoForme is unique in targeting both the primary and secondary prevention of CVD and removes several of the barriers to participating in a conventional CVD prevention program for French-speaking patients. FrancoForme is successful, receiving high satisfaction rates and resulting in significant improvements in cardiovascular risk factors, exercise, anxiety, and depression, as well as quality of life.

Le Programme régional des soins palliatifs de Sudbury : une réussite à souligner et à protéger - Racine, Guy (Reflets, 1999)
Parmi les programmes et les services de santé offerts à la population de la région de Sudbury, il en est un qui mérite une mention particulière tant par l’efficacité de son organisation que par la qualité du « caring » qu’on y exerce et c’est le Programme régional des soins palliatifs.

Affichage de postes bilingues dans la région de Kingston. Un guide utile pour les employeurs des secteurs de la santé et des services sociaux et communautaires | Job posting resource for bilingual positions in the Kingston area. A useful guide for employers in the healthcare and social community services sectors - Réseau des services de santé en français de l'Est de l'Ontario (A useful guide for employers in the healthcare and social community services sectors, 2019)

Je suis insatisfait(e) des services de santé reçus. Que faire ? Comment procéder ? [infographie] - Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada; Société Santé en français (2022)

Préparer le terrain. Soins de santé primaires en français dans le Sud de l'Ontario. Rapport régional - Réseau franco-santé du Sud de l'Ontario (2006)

Active offer of services in Canada’s official languages: development of a patient experience questionnaire - Sauvé-Schenk, Katrine; Pignac, Sarah; Kemenade, Solange; Savard, Sébastien; Prud'homme, Denis; Savard, Jacinthe (Journal of Communication in Healthcare, 2026)
ABSTRACT Background: In the bilingual Canadian context, the use of a preferred official language with healthcare providers is linked to optimized communication, respectful patient-centered care, improved safety and quality of services. This study aimed to develop and test a questionnaire that measures patients’ experience of how language was considered during an outpatient health encounter. Methods: French and English questions were drafted based on a literature review. Questionnaire content and flow were validated through focus groups with experts and service users. Question understanding and clarity was verified with cognitive interviews and pre-tests with diverse service users. The final questionnaire was pilot tested in three health organizations and temporal stability, and construct validity was verified. Results: Participants were nine anglophone and eleven francophone experts and service users for the focus groups, six anglophone and six francophone service users for the cognitive interviews, eleven anglophone and ten francophone service users for the pre-test. The resulting questionnaire has 31 experience-related questions organized under six themes: arrival/greeting, interpretation and translation services, language of health services, relationship with healthcare providers, visibility of official languages and follow-up. The questionnaire is completed online in French or English. The questionnaire was pilot tested with 199 participants in three sites. Temporal stability was moderate to good. Initial evidence of construct validity was demonstrated, suggesting that the questionnaire is adequate to evaluate patient experience. Conclusion: This questionnaire is the first known bilingual patient-experience tool, focused on the active offer of services in official languages during outpatient healthcare encounters, with preliminary validation.

Évaluation de la mise en œuvre de services en français en contexte minoritaire : développement d’un questionnaire sur l’expérience des usagers - Sauvé-Schenk, Katrine; Savard, Jacinthe; Savard, Sébastien; Prud’homme, Denis; van Kemenade, Solange; Le Callonnec, Lucie; Pignac, Sarah (2022)

Évaluation métrologique de la Mesure de l’offre active de services sociaux et de santé en français en contexte minoritaire - Savard, Jacinthe; Casimiro, Lynn; Benoît, Josée; Bouchard, Pier (Reflets, 2014)
Comment peut-on mesurer l’impact des actions entreprises pour améliorer l’offre active de services sociaux et de santé en français dans les communautés francophones en situation minoritaire? Un questionnaire mesurant premièrement les comportements individuels de l’offre active et deuxièmement la perception du soutien organisationnel à faire de l’offre active a été créé. La validité de contenu de la Mesure de l’offre active de services en françaisen contexte minoritaire a été établie à l’aide d’une recension d’écrits, de consultations menées auprès d’expertes et d’experts et d’un sondage Delphi pancanadien. Sa fidélité a été examinée à partir de données recueillies auprès de récents diplômés en santé et en service social. L’outil démontre une bonne consistance interne et des études auprès d’un plus large échantillon sont nécessaires pour augmenter la confiance envers sa stabilité temporelle. Il s’agit des premiers pas d’une démarche visant à mesurer l’évolution des comportements d’offre active à la suite d’activités de formation ou de changements organisationnels en faveur de services en français. Une telle mesure est aussi susceptible d’être utile dans les recherches visant à saisir les déterminants de ces comportements d’offre active. Mots-clés : Offre active de services en français, formation des professionnelles ou professionnels en santé et services sociaux, soutien organisationnel, évaluation, minorité, langue et services, qualité des soins et services, sécurité des clientes ou clients/patientes ou patients

Franc-O-Forme - Théberge, Sonia (Reflets, 1995)